2020
DOI: 10.46328/ijres.v6i4.1216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Online Peer-based Formative Assessments (PeerWise) to Enhance Student Learning in Physiology: A Systematic Review Using PRISMA Guidelines

Abstract: Due to the emerging demands on shifting focus towards the development of more student-centered and engaging learning experiences, this systematic review elucidates the effectiveness of PeerWise introduction into the blended learning model in Physiology education based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Twenty electronic databases were utilized to access related studies between years 2010 to April 2020. A total of eight recent articles on PeerWise in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…21 Studies of PeerWise use and impact come predominately from undergraduate STEM subjects (science, engineering, technology, and maths); many have shown positive correlations of overall PeerWise activity with examination results. [22][23][24][25][26] While it is difficult to disentangle the effect of the intervention from confounding factors such as other simultaneous learning activities and the intrinsic ability of students, studies in pharmacy, political science, accountancy, and STEM courses have shown improvements in assessments results when confounds such as previous academic performance are factored into the analyses. 13,[27][28][29] Attempts to determine which aspects of PeerWise use contributed to this positive correlation indicated that academic benefits arose from engaging across a range of activities.…”
Section: Pedagogical Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Studies of PeerWise use and impact come predominately from undergraduate STEM subjects (science, engineering, technology, and maths); many have shown positive correlations of overall PeerWise activity with examination results. [22][23][24][25][26] While it is difficult to disentangle the effect of the intervention from confounding factors such as other simultaneous learning activities and the intrinsic ability of students, studies in pharmacy, political science, accountancy, and STEM courses have shown improvements in assessments results when confounds such as previous academic performance are factored into the analyses. 13,[27][28][29] Attempts to determine which aspects of PeerWise use contributed to this positive correlation indicated that academic benefits arose from engaging across a range of activities.…”
Section: Pedagogical Principlesmentioning
confidence: 99%
“…26,31,32 Results from qualitative studies suggest that students found PeerWise an enjoyable learning experience which improved their learning competency, engagement with the materials, and motivation to learn. 26,31,32 Most interventions used PeerWise as a compulsory component of the curriculum, with engagement manipulated through inclusion of PeerWise exercises in summative assessment. 12,36,37 There remain contradictory reports, however, over whether medical students find compulsory MCQ writing exercises of educational benefit.…”
Section: Pedagogical Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the evaluation of Peer Wise in physiology courses, available data seem to be limited and incomplete with the current existing studies focused primarily on the association with academic performance and student perceptions. Therefore, the main focus of this review is to report comprehensively on the role of peer wise in supporting students' independent learning in physiology by further investigating the study characteristics, study designs, method of assessments, study limitations, and ultimately its effects on cognitive and affective performances (Khashaba, 2020).…”
Section: Similarly Field Practice In Building Education Program Of Faculty Of Engineering At Medan State Universitymentioning
confidence: 99%
“…PeerWise also includes a multiplechoice question bank as an additional learning tool for students. Teachers can use this feature to create or modify questions for future exams [9].…”
Section: Introductionmentioning
confidence: 99%